Citric acid-assisted accumulation of Ni and other metals by Odontarrhena muralis: Implications for phytoextraction and metal foliar distribution assessed by μ-SXRF. (May 2020) - do Nascimento, Clístenes Williams Araujo; Hesterberg, Dean; Tappero, Ryan; Nicholas, Sarah; da Silva, Fernando Bruno Vieira
Abstract: Odontarrhena muralis is one of the most promissing plant species for Ni phytomining, and soil amendments can further increase its Ni phytoextraction ability. Here we investigated whether Ni phytomining/phytoremediation using this Ni hyperaccumulator can benefit from applying citric acid to a serpentine soil that is naturally enriched in Ni (>1000 mg kg −1 ). Synchrotron micro X-ray fluorescence (μ-SXRF) was used to image Ni and other metal distributions in whole fresh leaves of O. muralis . Leaf Ni accumulation in plants grown on citric acid-amended soil increased up to 55% while Co, Cr, Fe, Mn, and Zn concentrations were 4-, 14-, 6-, 7- and 1.3-fold higher than the control treatment. O. muralis presented high bioconcentration factors (leaf to soil concentration ratio) to Ni and Zn whereas Cr was seemingly excluded from uptake. The μ- SXRF images showed a uniform distribution of Ni, preferential localization of Co in the leaf tip, and clear concentration of Mn in the base of trichomes. The citric acid treatments strongly increased the Co fluoerescence intensity in the leaf tip and altered the spatial distribution of Mn across the leaf, but there was no difference in Ni fluorescence counts between the trichome-base region and the bulk leaf. Our data from a serpentine soil suggests that citrate treatment enhances Ni uptake, but Co is excreted from leaves even in low leaf concentrations, which can make Co phytoming using O. muralis unfeasible in natural serpentine soils. Graphical abstract: Image 1 Highlights: Exogenous acid citric increases the Ni phytoextraction efficiency of O. muralis. Uptake of other metals is not a drawback for citric acid-assisted Ni accumulation. The accumulation of Mn in trichomes varies with the trichome position in the leaf. Manganese, Ni, and Co showed different accumulation patterns in O. muralis leaves. Abstract : Citric acid increased Ni accumulation by Odontarrhena muralis and changed the spatial distribution of metals in the leaf.